The Relationship Factors of Peers and the Role of Parents in Adolescent Smoking Behavior - Renna Oktavia Rudi; Wayan Aryawati; Agung Aji Perdana; Samino Samino (Jurnal Penelitian Pendidikan IPA, 2023)
One of the problems that often occur in adolescents is smoking-related problems. Smoking, seen from any point of view, is very harmful, both for oneself and those around one. Peer factors and the role of parents can influence adolescent smoking behavior. This study aimed to determine the relationship between peer factors and the part of parents and teenage smoking behavior at SMPN 3 Menggala, Tulang Bawang Regency, in 2023. The type of research in this research is quantitative, using analytic methods with a cross-sectional approach. The population in this study were all male students at SMPN 3 Menggala, Tulang Bawang Regency, in 2023, with a total of 127 students. The sampling technique used is total sampling. This research instrument uses a questionnaire. Data analysis used univariate and bivariate (chi-square). The results of this study indicate that 80 (63%) of respondents have positive behavior, 84 (66.1%) of respondents get support from peers, and 86 (67.7%) of respondents have a parental role. The chi-square test results found a relationship between peer factors (p-value 0.011 and OR = 2.875) and the part of parents (p-value 0.036 and OR = 2.423) with adolescent smoking behavior at SMPN 3 Menggala, Tulang Bawang Regency in 2023. Suggestions need to be supervised by strict regulations by the school regarding students' smoking habits and the provision of severe sanctions for those who are caught smoking.